The INFLUENCE OF INDUSTRIAL WORK PRACTICES (PRAKERIN) AND ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURIAL INTEREST IN STUDENTS OF SMK NEGERI 1 GOWA - Ardillah Fadillah; Fajriani Azis (Universitas Muhammadiyah Metro, 2025)
This study aims: (1) to analyze the effect of industrial work practices (prakerin) and entrepreneurship education simultaneously on entrepreneurial interest of students of SMK Negeri 1 Gowa, (2) to analyze the effect of industrial work practices (prakerin) and entrepreneurship education partially on entrepreneurial interest of students of SMK Negeri 1 Gowa, and (3) to identify the most dominant variable affecting entrepreneurial interest of students of SMK Negeri 1 Gowa. The population of this study are students of class XII Accounting and Financial Institutions (AKL) SMK Negeri 1 Gowa, while the sample is class XII Accounting and Financial Institutions (AKL) 2 taken with purpose sampling technique. The method used is Quantitative. Data collection is done using a questionnaire. Data analysis was carried out by Descriptive Analysis, Multiple Linear Regression Analysis, Multiple Correlation Coefficient Analysis (R), Hypothesis testing in the form of T Test (Partial) and F Test (Simultaneous). Based on the results of data analysis conducted, the results obtained Industrial work practices (prakerin) and entrepreneurship education simultaneously affect the entrepreneurial interest of students of SMK Negeri 1 Gowa. Industrial work practice (prakerin) partially has a negative and insignificant effect on entrepreneurial interest, and entrepreneurship education partially has a positive and significant effect on entrepreneurial interest of students of SMK Negeri 1 Gowa. Entrepreneurship education has a more dominant positive and significant effect on entrepreneurial interest of students of SMK Negeri 1 Gowa.